Development of plant cytosine base editors with the Cas12a system - Wang, Huanhuan; Liang, Jing; Chen, Like; Deng, Bufang; Gu, Dongfang; Liu, Xiaoshuang; Jin, Shan; Xu, Rongfang; Qin, Ruiying; Zhu, Yitong; Zhao, Liangxia; Kou, Dourong; et al. (The Crop journal, 2023)
Base editors of the Cas9 system have been widely used for precise nucleotide substitution in crops. In this study, Cas12a was applied to construct plant cytosine base editors (CBEs). The main elements of Cas12a-CBEs were engineered and their efficiency was evaluated in stably transformed rice cells. An optimized ttCas12a-hyA3Bctd editor, consisting of a LbCas12a variant carrying catalytic inactive D832A and temperature-tolerance D156R double mutations, a truncated human APOBEC3B deaminase, a human RAD51 single-stranded DNA-binding domain, and double copies of UGI, outperformed other Cas12a-CBEs in base editing efficiency. In T0 transgenic rice plants, ttCas12a-hyA3Bctd edited an average of 42.01% and a maximum of 68.75% of lines at six genomic targets. A-to-G conversions were generated in rice by an adenine base editor with a similar architecture to the optimized CBE. Our results provide preliminary evidence for the feasibility of robust and efficient plant Cas12a base editing systems, which could be useful for precise crop breeding.